EFEKTIVITAS TEKNIK PERSALINAN MC-ROBERT UNTUK MENINGKATKAN KEMAJUAN PERSALINAN PADA INPARTU KALA II - Oby, Robiah Adawiyah (Jurnal Ayurveda Medistra, 2024)
Childbirth is the process of discharging a fetus and placenta that has been for months or can live outside the womb by way of birth or by other means with help or without help. In the delivery stage when position setting has an effect on childbirth, such as the left oblique position is the best resting position, often used for urgent intervention, either to regulate duration at time two, or in the case of time two. It makes it easy to break between contractions during the end of time one and during the second delivery. There are also other positions such as Mc Robert, which are half-sitting positions with maximum hyperflexion on the pelvis by involving maximum flexion of the mother's legs until touching the abdomen.